Adaptive Informality in Platform Capitalism: From Reluctant Digitalization to Bold TikTok Commerce in Southern Italy - Orria, Brigida; Bellafronte, Sabrina (Italian Sociological Review, 2026)
This article rethinks informal economies as dynamic and generative components of capitalism, moving beyond definitions that treat them as marginal or deviant. Anchored in a Global South theoretical framework, based on qualitative methods and digital ethnography conducted in Naples and the Campania region, the study introduces the notion of “adaptive commerce” and “bold e-commerce”. We explore the evolving practices of informal trade across collaborative and hypervisible platforms such as Vinted and TikTok and delineate a continuum from discretionary, anonymized exchange to emotionally saturated, algorithmically mediated live commerce. The research outlines a shift from “reluctant digitalization”, marked by caution and anonymity, to “bold digitalization”, where exposure and performativity are embraced as economic assets. Three key points underpin this research: (1) the theorization of “bold digitalization” as a mode of platform-mediated informality marked by hyper-performativity and algorithmic visibility; (2) the identification of a platform governance spectrum, ranging from transactional discretion on Vinted to affective exposure on TikTok; and (3) the conceptual linkage between domestic labor, digital precarity, and economic spectacle. Informal economies, rather than resisting digital structures, actively shape and are simultaneously shaped by platform infrastructures, becoming central arenas of neoliberal experimentation. This reconceptualization challenges Eurocentric binaries of formal/informal and highlights informal economies as both zones of exploitation and engines of social creativity and economic innovation. The article calls for a critical reassessment of informal digital labor’s sustainability, gendered burdens, and potential to catalyze new socio-economic imaginaries.